Pedagogik oliy ta’lim muassasalarida o‘quv faoliyatida tajribalar natijalari tahlili (SCIENCE and SOCIETY, 2025)
This article analyzes the results of experimental teaching methods implemented in pedagogical institu- tions. The study examines the effectiveness of innovative approaches compared to traditional methods, focusing on skill acquisition, participant engagement, and learning activities. The results show that experimental methods significantly im- proved learning outcomes. The findings help improve pedagogical practice through evidence-based teaching innovations.